Study guides

Q: -5n minus 4p plus 7n plus 2?

Write your answer...

Submit

Related questions

6m + 5n - 4m + 7n = 2m + 12n

Assuming you meant 7n (not just 7 at the end of your question) - first... simplify the equation. Numbers raised to powers get priority - so your new sum is... 5n - 64n + 25n + n + 7n.... This simplifies to... -26n

1 - 7n = 15 - 5n Add 5n to each side: 1 - 7n + 5n = 15 -5n + 5n ie 1 - 2n = 15; subtract 1 from each side: -2n = 14 divide both sides by -2: n = -7

22n + 2.

9 - 5n

7n - 2 + 3n + 4 = 7n + 3n - 2 + 4 = 10n + 2 which can be simplified to 2(5n +1)

7n(n−1)

3n + 3(6 + 7n) = 3n + 18 + 21n = 24n + 18

7n + 1 = 6n + 8 7n=6n+7 (minus 1 from each side) n=7 (7n-6n equals n, you are left with n=7)

8n + 7 - n - 98 = 7n - 91

2-n-7n = 2-8n

-2.18

7n -1n,0n,1n,2n,3n,4n,5n,6n,7n 1 2 3 4 5 6 7 8 9

This might be the stable isotope of beryllium, 9Be: alpha + 9Be -> 12C + n alpha: 2p + 2n Be: 4p + 5n left side: 6p + 7n C: 6p + 6n right side: 6p + 7n Incidentally, this would not be a decay, rather an transfer reaction, I think.

It is 2n^3 + 7n^2 - 13n + 3

n(2n - 1)(2n + 7)

2N north

A variable comes after the number 2n+5n=7n

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals", "squared", "cubed" etc. Please use "brackets" (or parentheses) because it is impossible to work out whether x plus y squared is x + y2 of (x + y)2.

If the forces acting on an object are equal there is no motion (5N->O<-5N). If the forces are unequal there is movement (7N-->O<-5N).

12m + 3n - 6m + 7n6m + 10n

5n+2n=7n If the variable is the same, n, then you can add the coefficients, 5 and 2. In General an+bn=(a+b)n FOR A CASE THAT DOES NOT WORK. 5n+2m=5n+2m You cannot combine unlike variables

n > 2

The answer to 2N-4 time 7N plus 7 equals -10.50. This is a math problem.

This question as written can be taken two ways: 9m + 6n - 3m + 7n = 6m + 13n, or (9m + 6n) - (3m + 7n) = 9m + 6n - 3m - 7n = 6m - n